A method for locating fault sections of power optical communication network intelligent operation and maintenance equipment off-grid based on Dijkstra algorithm - Hailong ZHANG; Bo LI; Najuan JIA (Dianxin kexue)
In order to determine the mapping relationship between the off grid fault section and the fault current distribution, and find the shortest path between the off grid fault section and the fault current distribution, an off grid fault section location method based on Dijkstra algorithm was designed for the intelligent O＆amp;M equipment of the electro-optical communication network.The LightGBM algorithm in the data-driven method was selected to determine the mapping relationship between the off grid fault section and the fault current distribution through a large number of samples.Based on Dijkstra algorithm, the shortest path of mapping relationship was found, and the off network fault section was searched.The location platform for off grid fault section of intelligent operation and maintenance equipment of power optical communication network was designed to realize the location and alarm of off grid fault point, namely, signal loss of intelligent operation and maintenance equipment.The comparison experiment shows that the location result of this method was the closest to the actual location and the most accurate in the off network fault section location caused by the interruption of optical cable in the SDH ring network circuit area, the off network fault section location caused by the fault of optical cable in the multi way bus section, and the off network fault section location scenario caused by the fault of optical cable in the multi way bus section in the ring power area.It effectively improved the accuracy of fault location and has good applicability.